Tarihî Kapalı Çarşılara Alışveriş Merkezleri Literatüründen Bir Bakış - Faruk Bal; Murat Taşdemir (İnsan & Toplum)
!is study aims to shed a light on the question ‘to what degree shopping centers are continuation of Ottoman bazaars?’ by comparing two major shopping places of two different eras from various angles. To this end, locations, architecture, functions and management practices of the two shopping places are compared using related literature in economics. It is obvious that two shopping places have similarities as well as differences. Similarities seem to be the results of their economic functions. Differences, on the other hand, stems mainly from the differences in the economic environments in their time periods. !e main functions that shopping centers perform are the same as historical bazaars’. !erefore, the theories in the shopping centers literature explaining the existence of shopping centers are, also, able to explain the existence of historical bazaars.